A flexible electrode made of Ce-Al eutectic alloy grafted with MXene, its preparation method and application
By grafting the Ce-Al eutectic alloy electrode with the MXene layer on the surface, the problem of hydrogen dissipation and passivation of the aluminum foil negative electrode in aqueous solution is solved, and the electrochemical activity and structural stability are achieved, and the cycle life of the aluminum ion battery is extended.
Patent Information
- Application Number
- CN202210874806.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-25
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2042-07-25
AI Technical Summary
The aluminum foil negative electrode used in traditional aluminum ion batteries is prone to hydrogen evolution and passivation in aqueous solution, resulting in rapid failure of the battery, and the addition of alloy elements will generate intermetallic compounds that affect the processing performance of the electrode.
A Ce-Al eutectic alloy electrode with a layered sheet structure with a surface grafted MXene layer was used to alternately arrange the aluminum layer and the Al11Ce3 intermetallic compound layer, and combine the presence of the MXene layer to form a unique surface artificial SEI layer-layer sheet-shaped microcouple composite structure.
This material can suppress passivation, maintain smooth ion transport, realize a highly ordered reversible aluminum peeling/electroplating process, improve electrochemical activity and structural stability, and extend the cycle life of the battery.
Smart Images

Figure CN115117288B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of aqueous aluminum ion battery electrode materials, and specifically relates to a MXene-grafted Ce-Al eutectic alloy flexible electrode, a preparation method thereof, and an application thereof in aqueous aluminum ion batteries. Background Art
[0002] In the current global commercial battery field, lithium-ion batteries dominate with their high theoretical capacity. However, limited lithium resources have become a key factor restricting the development of lithium-ion batteries with the growing demand for energy storage devices, which has continuously pushed up the cost of lithium-ion batteries. In addition, the safety issues caused by the flammable and toxic organic electrolytes used in lithium-ion batteries have never been completely resolved. The limitations of lithium-ion batteries in applications have prompted researchers to continue to explore advanced energy storage devices with energy densities close to those of lithium-ion batteries. Batteries that use multivalent ion energy storage, such as aluminum ion batteries, zinc ion batteries, and magnesium ion batteries, have received widespread attention due to the higher charge load, smaller ion radius, and lower deposition potential of multivalent ions. Thanks to their unique advantages, multivalent ion batteries can use water-based electrolytes with higher ion conductivity and greater safety and achieve energy densities close to those of lithium-ion batteries. Among these multivalent ions, aluminum ion batteries, which have the highest theoretical energy density, naturally become the focus of current research.
[0003] Compared with current commercial lithium-ion batteries, batteries using water-based electrolytes have the advantages of low cost, high safety, environmental friendliness and low packaging equipment requirements. Commonly used positive electrode materials for aluminum-ion batteries include manganese-based oxides, carbon-based materials, Prussian blue analogs and organic positive electrodes, while the negative electrode usually uses commercial aluminum foil. Researchers have fully explored the positive electrode materials of aluminum-ion batteries, and these materials can show excellent stability in both aqueous and non-aqueous electrolytes. However, the aluminum foil negative electrode used in traditional aluminum-ion batteries is very prone to hydrogen evolution and passivation in aqueous solution, causing the battery to fail quickly, which greatly restricts the development of aqueous aluminum-ion batteries. In addition, in long-term cycles, dendrite growth and serious self-discharge problems on the surface of the aluminum foil negative electrode also threaten its long-term cycle stability. Since these problems are more serious in an aerobic environment, aqueous aluminum-based batteries can only be assembled under anaerobic conditions, which further weakens its advantages. Although the addition of alloying elements can improve the reversibility of aluminum negative electrodes in aqueous solutions, the formation of intermetallic compounds will seriously affect the processing performance of the electrode.
[0004] Adding cerium to aluminum alloys can inhibit the formation of dense passivation films, and at the same time, it can form aluminum-cerium intermetallic compounds and pure aluminum phases to form local galvanic pairs to promote the electrochemical stripping / electroplating process of the electrode. Since a small amount of cerium can reach the eutectic point to form an aluminum-cerium eutectic alloy with a regular nanostructure, this structure can maintain good mechanical processing properties. An artificial SEI layer can be formed by grafting a thin layer of MXene on the alloy surface, which can reduce the formation of oxides and inhibit the negative impact of by-product accumulation on cycle performance. The synergistic effect of alloying and artificial SEI layers can provide the possibility for mass preparation of aluminum ion battery negative electrodes that can be cycled stably for a long time. Summary of the invention
[0005] The purpose of the present invention is to overcome the problem that the aluminum foil negative electrode used in the above-mentioned aluminum ion battery is very likely to undergo hydrogen evolution and passivation in aqueous solution, causing the battery to fail rapidly, and the addition of alloy elements causes the formation of intermetallic compounds, which seriously affects the processing performance of the electrode, and to provide a MXene-grafted Ce-Al eutectic alloy flexible electrode, a preparation method and application thereof.
[0006] The technical solution of the present invention is to provide a Ce-Al eutectic alloy electrode with a lamellar structure and a MXene layer grafted on the surface. The Ce-Al eutectic alloy electrode with a lamellar structure is composed of an aluminum layer and an Al layer. 11 Ce3 intermetallic compound layers are stacked alternately, with the thickness of the aluminum layer being 0.16-0.72 μm and the thickness of the Al layer being 0.16-0.72 μm. 11 The thickness of the Ce3 intermetallic compound layer is 0.11-0.48 μm. The surface-grafted MXene layer is composed of interconnected single-layer MXenes with a thickness of 7-20 nm.
[0007] The optimal parameters are: the thickness of the aluminum layer is 0.24 μm, Al 11 The thickness of the Ce3 intermetallic compound layer is 0.16 μm, and the thickness of the surface-grafted MXene layer is 7-20 nm.
[0008] The specific steps of the method for preparing the Ce-Al eutectic alloy electrode with a lamellar structure and a surface-grafted MXene layer in the present invention are as follows:
[0009] 1) According to the eutectic point (attached to the instruction manual Fig.12 ) Determine the Ce-Al ratio, weigh the pure aluminum ingot and the pure ingot respectively, the pure aluminum block is 600-900g, and the purity is 99.994%; the pure cerium block is 96.4-144.6g, and the purity is 99.96%, and remove the surface oxide layer;
[0010] 2) Place the aluminum block in a corundum crucible, put it into a melting furnace protected by nitrogen, heat it to 800-1300℃ and keep it warm for 1-2h;
[0011] 3) After confirming that the aluminum block is completely melted, add the cerium block and continue to keep it at this temperature for 0.5-1.5 hours, stirring gently to ensure that the metal is completely dissolved and fully mixed;
[0012] 4) Pour the hot liquid metal into the mold and ensure that the metal solidifies at a cooling rate of 100-300K / s;
[0013] 5) Cut the completely cooled metal block into 400-500 μm thick metal sheets on a diamond wire cutting machine and grind off the surface oxide layer;
[0014] 6) using a rolling mill to roll the metal sheet into a metal sheet with a thickness of 50-100 μm;
[0015] 7) The metal sheet is immersed in a MXene dispersion with a concentration of 0.5 g / L for thirty minutes to prepare a Ce-Al eutectic alloy electrode with a lamellar structure and a surface-grafted MXene layer. The electrode is used as the negative electrode of an aqueous aluminum ion battery.
[0016] Beneficial effects of the present invention:
[0017] The preparation method of this material is simple, and at the same time, it provides an idea for a new type of negative electrode material for aqueous aluminum ion batteries. The Ce-Al eutectic alloy electrode with a lamellar structure and a surface grafted MXene layer provided by the present invention has a unique surface artificial SEI layer-lamellar microgalvanic composite structure, which enables it to achieve a highly ordered reversible aluminum stripping / electroplating process while inhibiting passivation and maintaining smooth ion transport. Compared with pure aluminum metal negative electrodes, symmetrical batteries prepared using eutectic alloy electrodes with a surface grafted MXene layer and aqueous aluminum ion full batteries have higher electrochemical activity and structural stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 , laser confocal image of Ce-Al eutectic alloy electrode with lamellar structure.
[0019] Figure 2 , Field emission electron microscopy (FESEM) image of a Ce-Al eutectic alloy electrode with a lamellar structure and a MXene layer grafted on the surface.
[0020] Figure 3 , XRD spectrum of the Ce-Al eutectic alloy electrode with a lamellar structure with a MXene layer grafted on the surface.
[0021] Figure 4 , EDS spectrum of the Ce-Al eutectic alloy electrode with a lamellar structure and a MXene layer grafted on the surface.
[0022] Figure 5, Schematic diagram of the electrode reaction of Ce-Al eutectic alloy with lamellar structure and surface grafted MXene layer.
[0023] Figure 6 The Ce-Al eutectic alloy electrode with a lamellar structure and a surface grafted MXene layer is composed of a standard symmetric battery with a current of 0.5 mA cm -2 Current density 1000h constant current charge and discharge test (voltage-time curve).
[0024] Figure 7 , the Ce-Al eutectic alloy electrode with a lamellar structure and a surface grafted MXene layer constitutes a standard symmetric cell electrochemical impedance spectroscopy (EIS).
[0025] Figure 8 , Ce-Al eutectic alloy electrode with lamellar structure grafted with MXene layer on the surface and Al supported by carbon cloth 0.09 Aqueous aluminum-ion full cells with standard MnO2 electrode composition were subjected to cyclic voltammetry (CV) tests at 0.1 mV s-1.
[0026] Fig. 9 , Ce-Al eutectic alloy electrode with lamellar structure grafted with MXene layer on the surface and Al supported by carbon cloth 0.09 Electrochemical impedance spectroscopy (EIS) was performed on standard aqueous Al-ion full cells composed of MnO2 electrodes in the frequency range of 100 kHz to 10 mHz.
[0027] Fig.10 , Ce-Al eutectic alloy electrode with lamellar structure grafted with MXene layer on the surface and Al supported by carbon cloth 0.09 The MnO2 electrode composition of the standard aqueous aluminum-ion full battery is 1A g -1 Cyclic stability test at current density of 2.5 %.
[0028] Fig.11 , Ce-Al eutectic alloy electrode with lamellar structure grafted with MXene layer on the surface and Al supported by carbon cloth 0.09 The MnO2 electrode composition is a standard aqueous aluminum ion full battery with a capacity of 0.1-5A g -1 Rate performance test diagram carried out at current density of .
[0029] Fig.12 , the proportion of Ce-Al eutectic alloy with lamellar structure grafted MXene layer on the surface is determined. DETAILED DESCRIPTION
[0030] The technical solution of the present invention is further explained and illustrated by way of specific embodiments below.
[0031] Example 1
[0032] The preparation process and steps in this embodiment are as follows:
[0033] A. Weigh 600g of pure aluminum block (Al, purity 99.994%) and 96.4g of pure cerium block (Ce, purity 99.96%), and remove the surface oxide layer.
[0034] B. Place the aluminum block in a corundum crucible, put it into a nitrogen-protected melting furnace, heat it to 1150°C and keep it warm for 2 hours.
[0035] C. After confirming that the aluminum block is completely melted, add the cerium block and continue to keep it at 1300℃ for 1 hour, stirring gently to ensure that the metal is completely dissolved and fully mixed.
[0036] D. Pour the hot liquid metal into a water-cooled copper mold and ensure that the metal solidifies at 300K / s.
[0037] E. Cut the completely cooled metal block into 400-500 μm thick metal sheets on a diamond wire cutting machine and grind off the oxide layer on the surface.
[0038] F. Using a rolling mill to roll the metal sheet into a metal sheet with a thickness of 50-100 μm;
[0039] G. Immerse the metal sheet in a MXene dispersion with a concentration of 0.5 g / L for thirty minutes to prepare a Ce-Al eutectic alloy electrode with a lamellar structure and a MXene layer grafted on the surface. The electrode can be used as the negative electrode of an aqueous aluminum ion battery.
[0040] Example 2
[0041] A. Weigh 900g of pure aluminum block (Al, purity 99.994%) and 144.6g of pure cerium block (Ce, purity 99.996%), and remove the surface oxide layer.
[0042] B. Place the aluminum block in a corundum crucible, put it into a melting furnace protected by nitrogen, heat it to 800℃ and keep it warm for 2 hours.
[0043] C. After confirming that the aluminum block is completely melted, add the cerium block and continue to keep the temperature at 800℃ for 1 hour, stirring gently to ensure that the metal is completely dissolved and fully mixed;
[0044] D. Pour the hot liquid metal into an insulated iron mold and ensure that the metal solidifies at 100K / s.
[0045] E. Cut the completely cooled metal block into 400-500 μm thick metal sheets on a diamond wire cutting machine and grind off the oxide layer on the surface.
[0046] F. Using a rolling mill to roll the metal sheet into a metal sheet with a thickness of 50-100 μm;
[0047] G. Immerse the metal sheet in a MXene dispersion with a concentration of 2 g / L for thirty minutes to prepare a Ce-Al eutectic alloy electrode with a lamellar structure and a MXene layer grafted on the surface. The electrode can be used as the negative electrode of an aqueous aluminum ion battery.
[0048] Verified by laser confocal microscopy, the thickness of the lamellae of high-temperature liquid metal cooled at a rate of 300K / s is distributed between 0.37-0.55μm, concentrated around 0.45μm.
[0049] Morphological and structural characterization of materials
[0050] Through laser confocal microscopy (CLSM) characterization, the smelted Ce-Al alloy sample showed a lamellar structure. Figure 1 , combined with field emission scanning electron microscopy (FESEM) such as Figure 2 The composite electrode sample has a lamellar structure inside and an ultra-thin MXene layer is grafted on the surface. The field emission scanning electron microscope energy spectrum test more intuitively proves that the alloy obtained by the present invention is a layer of aluminum and a layer of Al 11 Ce3 layers are arranged alternately and stacked, in which the thickness of the aluminum layer is ~0.24μm, and the thickness of Al 11 The thickness of the Ce3 layer is ~0.16μm, and the MXene layer on the surface shows a uniform distribution.
[0051] Figure 3 The XRD spectrum of Ce-Al eutectic alloy with lamellar structure grafted with MXene layer on the surface proves the eutectic phenomenon of Ce-Al alloy. In addition to the characteristic peak of MXene phase at low angle, only pure aluminum phase and Al 11 Ce3 metal compound phase. Figure 4 This is the EDS spectrum of the Ce-Al eutectic alloy with a lamellar structure with a MXene layer grafted on the surface. The measured chemical composition is shown in the following table.
[0052] element Wt% At% Al 85.39 96.41 Ce 13.62 2.96 Ti 0.99 0.63
[0053] The results show that the chemical composition of the lamellar alloy sample is Al 97 Ce3, combined with the Ce-Al binary alloy phase diagram, proves that the lamellar Ce-Al alloy sample is located at the eutectic point. At the same time, there is a very small amount of Ti on the surface of the alloy, which confirms the existence of a uniform MXene layer.
[0054] Electrochemical properties characterization results of materials
[0055] The Ce-Al eutectic alloy with a lamellar structure and a surface-grafted MXene layer prepared in Example 1 was cut into electrode sheets. The composite electrode sheet was then used as a working electrode and 2 mol L -1 Al (OTF) 3 solution was used as the electrolyte to form a standard symmetrical cell for electrochemical testing;
[0056] The Ce-Al eutectic alloy symmetric cell with a lamellar structure and a surface-grafted MXene layer prepared in Example 1 was charged at 0.5 mA cm -2 Current density for 1000h constant current charge and discharge test (voltage-time curve)
[0057] The Ce-Al eutectic alloy with a lamellar structure and a surface-grafted MXene layer prepared in Example 1 was subjected to an electrochemical impedance spectroscopy (EIS) test in a frequency range of 100 kHz to 10 mHz;
[0058] The Ce-Al eutectic alloy electrode with a lamellar structure and a MXene layer grafted on the surface in Example 1 was used as the negative electrode of the battery. 0.09 MnO2 electrode is used as the positive electrode of the battery, 2 mol L -1 of Al (OTF)3 and 0.2 mol L -1 Mn(OTF)2 solution was used as the electrolyte to form a standard aqueous aluminum ion full battery for electrochemical testing
[0059] The Ce-Al eutectic alloy electrode with a lamellar structure and a surface-grafted MXene layer prepared in Example 1 was connected to the Al 0.09 A standard aqueous aluminum ion full cell consisting of MnO2 electrodes was placed at 0.1 mV s -1 Cyclic voltammetry (CV) tests were performed at a scan rate of ;
[0060] The Ce-Al eutectic alloy electrode with a lamellar structure and a surface-grafted MXene layer prepared in Example 1 was connected to the Al 0.09 Electrochemical impedance spectroscopy (EIS) of aqueous aluminum-ion full cells with standard MnO2 electrode composition was performed in the frequency range of 100 kHz to 10 mHz;
[0061] The Ce-Al eutectic alloy electrode with a lamellar structure and a surface-grafted MXene layer prepared in Example 1 was connected to the Al 0.09 Aqueous aluminum-ion full cells with a standard MnO2 electrode composition were placed at 1 A g -1 The cycling stability test was carried out for 500 cycles at a current density of .
[0062] from Figure 6 The results of the symmetric cell show that the Ce-Al eutectic alloy symmetric cell with a lamellar structure and a grafted MXene layer on the surface has a high current density of 0.5 mA cm -2 The battery can be tested for more than 1000 hours without obvious voltage hysteresis at a current density of 1.547 W. In contrast, the pure aluminum symmetrical battery quickly showed severe voltage hysteresis at the beginning of the test. Figure 7 The impedance comparison of the pure aluminum symmetric cell and the symmetric cell with a lamellar structure of Ce-Al eutectic alloy electrode with a surface grafted MXene layer is shown in the figure. The charge transfer resistance of the symmetric cell with a lamellar structure of Ce-Al eutectic alloy electrode with a surface grafted MXene layer is about 163Ω. In comparison, the charge transfer resistance of the pure aluminum symmetric cell is about 3792Ω, which proves that the Ce-Al eutectic alloy electrode with a lamellar structure with a surface grafted MXene layer has stronger electrochemical activity than pure aluminum foil. Figure 8 It is a Ce-Al eutectic alloy electrode with a lamellar structure and a carbon cloth-supported Al 0.09 The aqueous aluminum ion battery composed of MnO2 electrodes has a voltage range of 0.5-1.9V and a charge transfer rate of 0.1mV s -1 The test curve was obtained at a scan rate of . The reduction peak of the battery redox curve appeared at 1.48V and the oxidation peak appeared at 1.65V. Fig. 9 The Ce-Al eutectic alloy electrode with a lamellar structure and the Al supported by carbon cloth were used in the frequency range of 100 kHz to 10 mHz. 0.09 Comparison of electrochemical impedance spectroscopy (EIS) under the composition of aqueous aluminum ions and pure aluminum foil in the MnO2 electrode. As can be seen from the figure, the charge transfer resistance of the full battery assembled using the composite electrode is only 86.21Ω. In contrast, the charge transfer resistance of the full battery using pure aluminum foil as the negative electrode is as high as 1857Ω. The small charge transfer resistance and polarization degree together illustrate that the alloy sample full battery has excellent electrochemical activity. Fig.10 The Ce-Al eutectic alloy electrode with a lamellar structure and the pure aluminum electrode with a MXene layer grafted on the surface are respectively connected with the Al supported by the carbon cloth. 0.09 The MnO2 electrode composition of the standard aqueous aluminum-ion full battery is 1A g -1 Cyclic curves at current density of 1.3 2.0 2.0 1.5 ... 0.09 When MnO2 electrodes are used to form aqueous aluminum ion batteries, the full battery can -1 After 500 cycles at a current density of 1.374 W, the battery capacity can still be maintained at more than 310 mAh g -1In sharp contrast, the aqueous aluminum-ion battery assembled with pure aluminum sheet electrodes basically failed after only 88 cycles, with only 17 mAh g -1 This fully demonstrates the unique advantages of the unique structure of the composite electrode in the cycle stability of aluminum ion batteries. Fig.11 Ce-Al eutectic alloy electrode with lamellar structure and Al supported by carbon cloth 0.09 The MnO2 electrode composition is a standard aqueous aluminum ion full battery with a capacity of 0.1-5A g -1 The rate performance test was carried out at a current density of 0.1A g -1 Increase to 5A g -1 The battery was able to retain more than 40% of its capacity when charged, demonstrating its excellent rate performance. Fig.12 Ce-Al eutectic alloy electrode with lamellar structure and Al supported by carbon cloth 0.09 Practical application diagram of aqueous aluminum ion full battery with standard MnO2 electrode composition. When the battery is bent to a certain angle, it can still drive a small electric fan, which shows that it has excellent mechanical properties and flexible application prospects. The above performance tests all show that the Ce-Al eutectic alloy composite electrode with a lamellar structure and a surface grafted MXene layer can be used as an aqueous aluminum ion battery negative electrode in the field of aqueous batteries and shows good application prospects. The method of the present invention can also be extended to other energy storage battery systems, providing a new method and idea for improving the electrochemical activity and structural stability of metal electrodes.
Claims
1. A Ce-Al eutectic alloy electrode with a MXene layer grafted on the surface, characterized in that: The electrode surface is a surface-grafted MXene layer, and the electrode is composed of an aluminum layer and an Al 11 Ce3 intermetallic compound layers are stacked alternately, with the thickness of the aluminum layer being 0.16-0.72 μm and the thickness of the Al layer being 0.16-0.72 μm. 11 The thickness of the Ce3 intermetallic compound layer is 0.11-0.48 μm, and the surface-grafted MXene layer is composed of interconnected single-layer MXenes with a thickness of 7-20 nm.
2. The method for preparing a Ce-Al eutectic alloy electrode with a surface grafted MXene layer as claimed in claim 1, wherein the specific steps are as follows: 1) Determine the Ce-Al ratio according to the eutectic point, weigh pure aluminum ingots and pure cerium ingots respectively, and remove the surface oxide layer; 2) Place the aluminum block in a corundum crucible, put it into a melting furnace protected by nitrogen, heat it to 800-1300℃ and keep it warm for 1-2h; 3) After confirming that the aluminum block is completely melted, add the cerium block and continue to keep it at this temperature for 0.5-1.5 hours, stirring gently to ensure that the metal is completely dissolved and fully mixed; 4) Pour the hot liquid metal into the mold and ensure that the metal solidifies at a cooling rate of 100-300K / s; 5) Cut the completely cooled metal block into 400-500 μm thick metal sheets on a diamond wire cutting machine and grind off the surface oxide layer; 6) using a rolling mill to roll the metal sheet into a metal sheet with a thickness of 50-100 μm; 7) The metal sheet is immersed in a MXene dispersion with a concentration of 0.5-3 g / L for 10-50 minutes to prepare a Ce-Al eutectic alloy electrode with a lamellar structure and a surface-grafted MXene layer, which can be used as the negative electrode of an aqueous aluminum ion battery.
3. The method for preparing a Ce-Al eutectic alloy electrode with a surface grafted MXene layer according to claim 2, characterized in that: Step 1) The Ce-Al ratio is determined according to the eutectic point.
4. The method for preparing a Ce-Al eutectic alloy electrode with a surface grafted MXene layer according to claim 2, characterized in that: Step 1) The pure aluminum ingot is 600-900 g, with a purity of 99.994%; the pure cerium ingot is 96.4-144.6 g, with a purity of 99.96%.
5. The use of the electrode according to claim 1, characterized in that: Used as the negative electrode of aqueous aluminum ion batteries.
Citation Information
Patent Citations
Method for preparing cerium dioxide / two-dimensional layered titanium carbide composite material through hydrothermal process
CN105536833A
Zn-Al eutectic alloy electrode with a lamellar structure and preparation method thereof and application thereof in aqueous zinc ion battery
CN110620225A